Apelin/APJ system: A potential therapeutic target for endothelial dysfunction‐related diseases. Issue 8 (26th December 2018) - Cheng, Jun; Luo, Xuling; Huang, Zhen; Chen, Linxi
Abstract: APJ is a G protein‐coupled receptor and its endogenous ligand is apelin. Studies have shown that apelin/APJ system is widely distributed in the body, especially highly expressed in the vascular endothelial cells (ECs). Numerous reports have demonstrated that apelin/APJ system plays an important role in the regulation of ECs function. Our lab has demonstrated that apelin‐13 is able to promote adhesion of monocyte‐human umbilical vein EC via 14‐3‐3, and reactive oxygen species‐autophagy signaling pathways. In this review, we concentrate on the regulatory mechanism of apelin/APJ system in EC, including promotion of proliferation, migration, and angiogenesis. Moreover, we also analyze the role of apelin/APJ on endothelial dysfunction‐related diseases including atherosclerosis, diabetes, hypertension, and myocardial infarction. Finally, we summarize the most commonly used agonists and antagonists of APJ. Therefore, apelin/APJ system is expected to be a therapeutic target for the treatment of endothelial dysfunction‐related diseases. Abstract : This review summarizes the link between the apelin/APJ system and EC dysfunction‐related diseases, providing ideas for future treatment of the disease.